Framework for multi-stressor physiological response evaluation in amphibian risk assessment and conservation - Awkerman, Jill A.; Glinski, Donna A.; Henderson, W. Matthew; Meter, Robin Van; Purucker, S. Thomas (Frontiers in Ecology and Evolution, 2024)
Controlled laboratory experiments are sometimesoften performed on amphibians to establish causality between stressor presence and an adverse outcome. However, in the field, identification of lab-generated biomarkers from single stressors and the interactions of thesemultiple impacts are difficult to discern in an ecological context. The ubiquity of some pesticides and anthropogenic contaminants results in potentially cryptic sublethal effects or synergistic effects among multiple stressors. Although biochemical pathways regulating physiological responses to toxic stressors are often well-conserved among vertebrates, different exposure regimes and life stage vulnerabilities can yield variable ecological risk among species. Here we examine stress-related biomarkers, highlight endpoints commonly linked to apical effects, and discuss differences in ontogeny and ecology that could limit interpretation of biomarkers across species. Further we identify promising field-based physiological measures indicative of potential impacts to health and development of amphibians that could be useful to anuran conservation. We outline the physiological responses to common stressors in the context of the altered functional pathways, presenting the most useful stage-specific endpoints for anuran species, and discussing multi-stressor vulnerability in the larger framework of amphibian life history and ecology. This overview identifies points of physiological, ecological, and demographic vulnerability to provide context in evaluating the multiple stressors impacting amphibian populations worldwide for strategic conservation planning.Multiple common sources of physiological stress contribute to the ubiquitous threats to amphibian populations worldwide, including disease, pollution, and habitat loss as well as combinations of these stressors, which vary geographically (Stuart et al. 2004, Wake and Vrendenburg 2008, Foden et al.